Social computing and social media : 7th International Conference, SCSM 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: 7th International Conference, SCSM 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. (2015) - Unknown
No abstract available